Transplacental transmission in cattle: is Toxoplasma gondii less potent than Neospora caninum - Jitbanjong Wiengcharoen (2015)
We compared the transplacental-transmission ability of Toxoplasma gondii and Neospora caninum in cattle. One uninfected pregnant heifer served as control, while three were inoculated with N. caninum K9WA strain and four with T.gondii RH strain at their midgestational period. Both infected groups showed clinical signs and antibodies either to N. caninum or T. gondii, while the control animal was normal. Two (50%) Toxoplasma dams aborted on days 6 and 11 postinoculation. T. gondii tachyzoites were found in various organs of those dams that had abortions but not in their fetuses. Two Neospora dams did not abort but gave birth to subclinically infected calves. The remaining two Toxoplasma dams and one from Neospora group became recumbent. Those two dams and their fetuses showed disseminated Toxoplasma DNA, but no Neospora DNA was found. Our findings suggest that maternal toxoplasmosis could be a cause of abortion and congenital toxoplasmosis in cattle, especially when they are infected by virulent strains.